PENGARUH MEKANISME GCG TERHADAP PENGUNGKAPAN CSR PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BEI - Agus Riyanto; Devy Putri Milanda; Reslianty Rachim; Novita Dewi; Abdi Kurniawan (University of Widya Gama Mahakam Samarinda, 2024)
The aim of this research is to determine the influence of Good Corporate Governance (GCG) mechanisms on Corporate Social Responsibility (CSR) disclosure in coal mining sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data collection technique used purposive sampling totaling 19 companies. This research uses multiple linear regression analysis with the help of the SPSS Ver 29 computer program. The research results show that Managerial Ownership has a positive and insignificant effect on CSR Disclosures, Institutional Ownership does not affect CSR Disclosures, the Board of Commissioners positively and significantly influences CSR Disclosures, the Audit Committee and the Board of Directors have a negative and significant effect on CSR Disclosures in listed mining sub-sector companies on the IDX for the 2018-2022 period. Simultaneously Managerial Ownership, Institutional Ownership, Board of Commissioners, Audit Committee and Board of Directors positively influence CSR Disclosure in mining sub-sector companies listed on the BEI for the 2018-2022 period